Examination of the reaction of a macromolecular sulfonamide with sodium nitrite in acidic media - Bogoczek, R.; Kociołek-Balawejder, E.; Stanisławska, E. (Polimery, 2022)
In this study we have examined the reaction of macromolecular sulfonamide (styrene/divinylbenzene copolymer with the macroporous structure containing -SO2NH2 groups) with nitrites in acidic media. We found that the lowest admissible pH of the reaction medium providing the stability of the functional groups was 4.0. The lower the pH, the quicker the functional group lost its nitrogen atom and transformed to a sulfonic group. Knowledge of the chemical stability of sulfonamide groups in the presence of nitrites is not only of cognitive but also of practical value, because N-chloro derivatives of a sulfonamide copolymer (containing so-called active chlorine) are useful for the elimination of nitrites from waters through their oxidation to less toxic nitrates.